Perkawinan Sedarah Suku Polahi Ditinjau dari Undang-Undang Nomor 16 Tahun 2019 - Nurul Qomaril Afifah; Ikfi Rizkina (Journal of Law, Society, and Islamic Civilization, 2022)
This research tries to explain incest in the Polahi tribal tribe, who dwell among the interior woods of Gorontalo, more specifically in the forests of the Boliyohuto region, Tamaila Village, Tolangohula District, Gorontalo Regency, a culture that is deeply rooted in the local population. The research technique employed is prescriptive and applied normative legal research. Primary and secondary legal documents, as well as literary and document studies, were utilised as sources of legal materials. In the Polahi tribe, inbreeding occurs when a person reaches maturity (both male and female) and is matched with their own siblings. Inbreeding is illegal in marriage, according to the conclusions of this research, under Law Number 16 of 2019 about Amendments to Law Number 1 of 1974 Concerning Marriage, which stipulates that marriage is prohibited between two persons connected by blood, breast milk, and marriage. As a result, the Polahi Tribe has been found to have broken Article 8 of the Marriage Law. If the husband and wife knew before they married that inbreeding was banned by law or religion, the marriage would be considered illegal, and the child's status would be void. As a result, the kid that is born only has a favourable position in terms of inheriting and supporting the original mother and her family. Meanwhile, the government, in this instance the Gorontalo Regency Government, is working to eliminate the practise of inbreeding within the Polahi Tribe's customary law group. The situation of children born from incestuous marriages because their parents were unaware that their union broke the marriage restriction is still relevant. In the meanwhile, if both parties are aware that the marriage is prohibited under Shari'a, the marriage must be cancelled. If they do not end the marriage, it becomes a legal marriage, and the child's status becomes invalid. As a consequence, children that are born are only in a better position to inherit and support their birth mother and family.